PENGARUH PEMBIAYAAN AKAD MUSYARAKAH DAN AKAD IJARAH TERHADAP TINGKAT KEUNTUNGAN PERSEROAN TERBATAS BANK PEMBIAYAAN RAKYAT SYARIAH MANDIRI PERIODE 2003-2017 - GIVI ELGIVIA; WAHIDIN MUSTA’IN BILLAH; DINA WULANDARI (DIRHAM Jurnal Ekonomi Islam, 2020)
This Study analyze the effect of musyarakah financing and ijarah financing on profitability level at Bank Mandiri Syariah by using ROA ( Return on Asset)ratio. The research method used is descriptive research of quantitative approach anc case study at Bank Syariah Mandiri. The type of data obtained from this research is secondary data based on the result of the financial report of Bank Syariah Mandiri linked and through the website www.ojk.go.id Analyzer used in multiple linear regression analysis. The sampling technique used was purposive sampling. The sample has 15 accounting reports that meet the determined criteria. Through fifteen years of observation period starting from the year 2003 to 2017 the unit of analysis obtained is a financial statement of an accounting report. The research variable consisted of independent variables in the form of musyarakah financing (X1), Ijarah financing (X2), and influence to profitability level (Y). These variables were tested with multiple linear regression analysis with 5% if significance level. Analysis technique data used is partial statistical analysis (Ttest) and Simultaneous statistical analysis (Ftest). The result of this research indicated that Musyarakah financing and Ijarah financing did not partially have an effect on profitability with the Tcount value of 3,987 Musyarakah financing and 2,343 Ijarah financing. the result simultaneous by F test is known that simultaneously Musyarakah financing and Ijarah financing does no effect the stock price with the value Fcount value of 8,419 which is lower than Ftable score 3,81